THE STATE OF MUCOSAL IMMUNITY AND MICROBIOCENOSIS OF THE GENITOURINARY TRACT IN PATIENTS WITH CHRONIC RECURRENT PYELONEPHRITIS - O. Romanenko; N. Stepanova; A. Rudenko; V. Kruglikov; O. Kornilina; L. Lebid; M. Kolesnyk (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim - to examine the state of mucosal immunity and microbiocenosis of the genitourinary tract in patients with chronic pyelonephritis (PN) and determine their significance as risk factors of recurrences. Material and methods. In this research some 36 women mucosal immunity with recurrent PN had been investigated. Its peculiarities with the patients with recurrent PN (n=22) in comparison with relatively-healthy donors (n=12) as well as in comparison with sporadic disease (n=14). Some 16 females were investigated of biocenosis of vagina by the PLR real-time method. The material of the research was urine as well as scrapes of urethra and the cervical channel. The results of the research. The analysis of the quantity of microflora of vagina has indicated decreasing of Lactobacillus spp. In majority – 12 (75%) of the patients. During the investigations of hypostatis liquid of vagina the patients with PN, decreasing of intensity of phagocytosis of neutrophiles and macrophagus was indicated (р<0.001 and р=0.004, respectively), as well as increasing of phagocytosis activity of monocytes/macrofagus (р=0.01). The indicator of activation of neutrophiles as well as concentration Ig M surely high in the patients with S. faecalis in vagina (U=9.0; р=0,03 and ρ=0.64; р=0.007 respectively). The levels of lysozyme and lactoferrin in the urine of patients with pyelonephritis were significantly higher than those of conventionally healthy women (11.5 (1.7-27.1) vs 0.9 (0-1.2) ng/ml; р<0.001 and 5 (0-43) vs 0 (0-0)р=0.004). sIg A concentration was significantly (p=0.008) reduced in the vagina of women with recurrent PN, whereas the level of lysozyme was significantly (p = 0.003) increased. In scrapings from the cervical canal was determined limits the intensity of spontaneous NBT reaction of neutrophils (p = 0.04).The recurrence rate of PN was significantly correlated with number of Lactobacillus spp. in the vagina (r=-0.6244; p=0.0074), and with the intensity of the metabolic monocytes potential that were isolated from the vagina (ρ=0.53; p=0.01), and with the urinary lysozyme concentration (r=0.378; p=0.03), and with Ig G concentration of in the vaginal washings (ρ=-0,46; p=0.001).Conclusions. Vaginal dysbiosis in patients with recurrent PN is a major cause of reducing the barrier properties of the mucosa of the urogenital tract. Imbalance of local immunity is determined a violation of functional reserve oxygen dependent metabolism of phagocytic cells and the lack of local produce sIg A and Ig G against a background of increased secretion of lysozyme in the urine and the vagina.